Bestrophin-encoded Ca²⁺-activated Cl⁻ channels underlie a current with properties similar to the native current in the moth Spodoptera littoralis olfactory receptor neurons. - Adrien François (Public Library of Science (PLoS), 2012)
Responses of insect olfactory receptor neurons (ORNs) involve an entry of Ca²⁺ through olfactory heterodimeric receptor complexes. In moths, the termination of ORN responses was found to strongly depend on the external Ca²⁺ concentration through the activation of unknown Ca²⁺-dependent Cl⁻ channels. We thus investigated the molecular identity of these Cl⁻ channels. There is compelling evidence that bestrophins form Cl⁻ channels when expressed in heterologous systems. Here we provide evidence that antennae of the moth Spodoptera littoralis express three transcripts encoding proteins with hallmarks of bestrophins. One of these transcripts, SlitBest1b, is expressed in ORNs. The heterologous expression of SlitBest1b protein in CHO-K1 cells yielded a Ca²⁺-activated Cl⁻ current that shares electrophysiological properties with the native Ca²⁺-activated Cl⁻ current of ORNs. Both currents are anionic, present similar dependence on the intracellular Ca²⁺ concentration, partly inactivate over time, have the same anion permeability sequence, the same sequence of inhibitory efficiency of blockers, the same almost linear I-V relationships and finally both currents do not depend on the cell volume. Therefore, our data suggest that SlitBest1b is a good candidate for being a molecular component of the olfactory Ca²⁺-activated Cl⁻ channel and is likely to constitute part of the insect olfactory transduction pathway. A different function (e.g. regulation of other proteins, maintenance of the anionic homeostasis in the sensillar lymph) and a different role (e.g. involvement in the olfactory system development) cannot be excluded however.